G429(P) SMOF parenteral nutrition is an effective option in the long term nutrition of preterm infants and associated with less cholestatic jaundice. (27th April 2016) - Rajagopal, P; Holliday, K; Skinner, A
Abstract : Introduction: Nutrition in preterm infants presents unique challenges and enteral feeding strategies alone are invariably insufficient particularly in the early weeks after birth. The use of standard parenteral nutrition (PN) solutions is associated with the development of PN associated cholestasis (PNAC). The use of standard parenteral nutrition (PN) is associated with the development of PN associated Cholestasis. Intralipid (which contains soybean oil, egg yolk phospholipids and Glycerin) is widely used in PN regimes. In recent years another formulation based on soybean oil, medium chain triglycerides MCT, olive oil and fish oil (SMOF) has become available. SMOF has more favourable omega 3:6 ratio than Intralipid. In our unit, we changed our lipid supply from Intralipid to SMOF based PN in November 2010 and subsequently analysed its use and impact on liver function tests in a series of preterm infants. Methods: A retrospective study of preterm infants requiring PN for more than 2 weeks was conducted. Two study periods were scrutinised; one from January 2010 to November 2010 during the phase of Intralipid use, and the second period following introduction of SMOF, from January to December 2014 . As a part of the PN regime SMOF was commenced at 1 g/kg/day on day 1 of life building up to a maximum of 3 g/kg/day by Day 3. The study population consisted of babies born less than 32 weeks who required PN for more than 2 weeks. Information about liver function was obtained from routine biochemical reports in the patients' case notes and diagnosis of PNAC was made when conjugated bilirubin exceeded 1.5 mg/dl. Patient data was analysed and the occurrence of PNAC noted. Statistical analysis was performed using Fisher's exact test. Results: In the first study period, 16 preterm infants (median birthweight 900 gram) fulfilled inclusion criteria. Ten of these patients (63%) developed cholestatic jaundice. During the second phase, SMOF was utilised in 34 patients (median birthweight 820 gram), of whom 7 patients (26%) developed cholestatic jaundice. This difference was statistically significant (p = 0.008; Fisher's exact test). There was no difference in the growth rate or time to full enteral feeds between the two groups. Conclusion: Our data shows that PN regimes including SMOF lipid are well tolerated in the preterm population and offer the added advantage of having less incidence of cholestatic jaundice.